Work-Family Conflict: Studi Fenomenologi Pada Pegawai Perempuan Sebagai Minoritas Gender Di Lingkungan Kerja Maskulin: Studi Pada Pegawai Perempuan Di Kantor Regional PT Perkebunan Nusantara I Regional - Sarasifa Mashia Hermawanputri; Aulia Vidya Alamadana (Diponegoro Journal of Management, 2026)
This study is grounded in the increasing participation of women in the formal workforce, which is not accompanied by a proportional redistribution of domestic responsibilities, thereby intensifying Work-Family Conflict (WFC). The complexity of this phenomenon is further heightened in maledominated organizational contexts that are embedded with patriarchal norms and values. This study aims to explore the lived experiences of female employees and the meanings they construct regarding WFC within such environments.This research employs a qualitative approach using Heideggerian hermeneutic phenomenology to capture participants’ subjective experiences. Data were collected through in-depth interviews with married female employees at the Regional Office of PT Perkebunan Nusantara I Regional 3 and analyzed interpretatively using NVivo 12. The findings demonstrate that WFC is not merely shaped by time-, strain-, and behavior-based dimensions, but is also deeply influenced by structural gender dominance embedded in organizational practices. Three major themes emerged: (1) the constructed meaning of WFC, (2) the lived reality of a masculine workplace, and (3) self-adjustment as a strategic response to sustain both work and family roles.